Avaliação de concretos reforçados por confinamento com manta de fibra de vidro estrutural e pré-impreganada - Pereira, Fábio Sérgio da Costa (2009)
Due to the occurrence of diseases in the use of structural reinforcements in composites, with presentation of concrete blanket detachment, has been identified the need to evaluate the performance of concrete reinforced with glass fiber. This study aims to evaluate these concretes by means of testing methodologies, using concrete with low resistance with structural reinforcement for confinement by preimpregnated glass fiber and traditional fiberglass blanket. The first stage of work was the development of methodologies for analysis, opting for four types, such as the acoustic survey, strength to compressive, the pull-off and ultrasound. Next, tests were carried out using the four selected methodologies in 30 of proof-of-specimens by 5x10 cm, 15 were reinforced with the traditional fiberglass blanket with 5specimens exposed to test a marine environment of marine coastline of Natal-RN and 15 were reinforced with a pre-impregnated glass fiber blanket, as well as 5specimens exposed to a test environment of the marine coastline of Natal-RN. After conducting the acoustic survey, it has been verified a lack of delaminating and air bubbles in the samples, confirming the absence of gross shortcomings in the implementation of the ribs both the traditional fiberglass blanket and in the preimpregnated fiber glass blanket. After carrying out methods of pull-off and compressive strengthening test it was observed that the reinforced proof-bodies with pre-impregnated glass blanket showed maximum stresses higher than the traditional fiberglass blanket; consequently a greater grip with the formation of a smaller area of . fracture, unlike traditional glass mat, which showed lower maximum stresses, with a greater area of fracture. It was also found that the traditional fiberglass blanket presented detachment of blanket-concrete interface, unlike the pre-impregnated fiberglass blanket, which showed a better grip on the blanket-concrete interface. In the trial of ultrasound there was no presence of cracks in the blanket-concrete interface, yielding to both blankets good compactness of the concrete. At the end of this work, they were developed and proposed two methods of testing for evaluation of reinforced concrete structures with composites, for standardization, the acoustic survey and pull-off